A study of laryngeal microsurgery for vocal cord lesions - Zafar, Shaheen; Kumar, Rohit (Asian Journal of Medical Sciences, 2022)
Background: A voice disorder occurs when a person’s voice quality, pitch, or volume is out of synch with their age, gender, culture, or location. Moreover,when a person shows concern about an unusual voice that does not satisfy daily necessities, despite the fact that others do not notice, it is considered to have voice problem. Aims and Objectives: Collection and analysis of data base to determine the impact of microlaryngeal surgery (MLS) on voice outcome. Materials and Methods: The study was carried out in the Department of Otorhinolaryngology, in a tertiary care hospital in Patna Medical College andHospital, from October 2020 to June 2021. Study was performed on 30 consecutive cases of benign lesions of vocal cord diagnosed clinically not responding to medical management. Results: Voice handicap index was evaluated preoperatively and postoperatively. The results were compared. Preoperatively, 40% (12) of patients showed moderate handicap scoring and 60.0% (18) patients showed severe handicap index. Postoperatively, there was improvement. At 2nd, follow-up 33.3% (10) patients showed moderate handicap scoring, 50.0% (15) patients showed mild handicap scoring and 16.7% (5) patients showed severe handicap scoring. At 6th week follow-up 21, (70.0%) patients showed mild handicap scoring and 30.0% (9) showed moderate handicap scoring. Finally, at 12th week follow-up, we observed 93.3% (28) patients had mild handicap scoring while only 6.7% (2) patients had moderate handicap scoring with significant difference (P≤0.0001). Conclusion: MLS is an effective procedure to provide improvement in speech among patients with benign vocal cord lesion.